Planning For Intergenerational Recreation Program For Thai Elderly (Journal of Namibian Studies : History Politics Culture, 2023)
Purpose: The purpose of this research was to explore attitude, behavior and needs towards recreation activities among Thai elderly and to find out the guidelines for Intergenerational Recreation Program for elderly. Mixed methods was used in this research consisted of the attitude and need toward recreation activities of Thai elderly survey collected from 470 Thai elderly and in-depth interview focused on 8 elderly and 8 children (age 5-12) of Muban Laem Thong Niwet to understand recreation participation behavior, interested and attitude towards intergenerational recreation activities. The researcher found that, the most popular recreation activity is the cultural special events 67.8% and the most wanted activity for elderlies to do is volunteer activities 31.5%. All elderly and children have a good attitude towards the intergenerational recreation program and want to be a part of the program. The suitable activities used in the program are the activities that the elderly and the young can have fun together and can improve all dimensions of holistic health including physical health, mental health, social health, spiritual health and also improve elderly’s quality of life. The outcomes of the study were used as basic information and guidelines for establishing an intergenerational recreation program for elderly which suitable for Thai society. There are many studies in Thailand about a recreation program for elderly, but no study used the benefit of Thai culture and lifestyle that young children and old spend time together, to create a program before.